The Difference Denominations Made: Identifying the Black Church(es) and Black Religious Choices of the Early Republic. Issue 2 (2019) - Bulthuis, Kyle T.
ABSTRACT: Scholars of African-American religious history have recently debated the significance of the black church in American history. Those that have, pro and con, have often considered the black church as a singular entity, despite the fact that African Americans affiliated with a number of different religious traditions under the umbrella of the black church. This article posits that it is useful to consider denominational and theological developments within different African-American churches. Doing so acknowledges plural creations and developments of black churches, rather than a singular black church, which better accounts for the historical experience of black religion. In this piece, I analyze four different denominational and theological traditions that blacks followed in the early Republic: the Anglican–Episcopalian, the Calvinist (Congregational–Presbyterian), the Methodist, and the Baptist. Each offered a unique ecclesiastical structure and set of theological assumptions within which black clergy and laity operated. Each required different levels of interaction with white coreligionists, and, although some tended to offer more direct opportunities for reform and resistance, all groups suffered differing constraints that limited such action. I argue that the two bodies connected to formalist traditions, the Episcopalian and Calvinist, were initially better developed despite their smaller size, and thus disproportionately shaped black community and reform efforts in the antebellum United States.